Successful Aging at Work: Organizational Strategies and Employee Experiences in Public and Private Sector - Ferjan, Maruša; Debelak, Katja (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
Successful aging at work (SAW) has become a critical challenge for contemporary organizations. This study examines SAW from two complementary perspectives: organizational practices aimed at supporting aging employees (SAW strategies) and employees’ maturation, development, and growth through aging in organizational contexts (SAW experiences). Using survey data from 456 employees in Slovenia, we compare public and private sector organizations and examine the relationship between SAW strategies and experiences. Results show that SAW strategies are widely implemented, with no significant differences between sectors. While the strategy–experience correlation is stronger in private sector organizations, SAW experiences are significantly more positive in public sector organizations. The possibility to remain employed in an organization as long as desired is most strongly associated with SAW experiences, which suggests that job security plays an integral role in supporting positive aging trajectories and acts as a foundation that enables employees to adapt, develop, and thrive as they age.